Gas-oxygen cutting of continuous cast slugs at MNLZ-3 RUP BMZ - A. A. Pirogov; V. D. Kodra (Литьë и металлургия)
There is given information on operation of the autogenous equipping for gas-oxygen cutting of continuous cast slugs, installed as a result of modernization of MNLZ- 3 RUP “BMZ‘'. The reliability and safety of operation of the offered construction of the machine for gas-oxygen cutting of slugs produced by ОA ‘'Effect‘' (Odessa) is proved.